Optimization of self-assembled carbon nanotube array with Langmuir-Blodgett technique - Muhammad Za'im Zamzam (Nanyang Technological University, 2022)
Carbon Nanotubes (CNTs) are of tubular structures made of a graphene sheet with a diameter from 1nm up to a few tens of nanometers. Only from the architecture, a CNT can be regarded as a sheet of graphene rolled up along a crystalline orientation. CNTs can be aligned to form arrays for electronic applications, such as the channel material for field-effect transistors (FETs), etc. Compared to CNTs network channels, the aligned CNT array channel can offer outstanding on-state current and driving capacity for FETs due to the significant reduction of inter-tube junctions. Among the self-assembly methods for CNT alignment, the Langmuir-Blodgett (LB) technique has been shown to be successful in producing highly packed aligned CNT arrays. However, there are insufficient studies on the optimization of the parameters and procedures of the LB technique leads to fabrication of highly packed aligned CNT arrays. Therefore, this project aims to investigate the influences of several parameters (e.g, compression/expansion cycles, barrier speed, dipping speed, etc.) on CNT alignment using the LB technique.